Elastic and electrical properties and permeability of serpentinites from Atlantis Massif, Mid-Atlantic Ridge. Issue 2 (14th August 2017) - Falcon-Suarez, Ismael; Bayrakci, Gaye; Minshull, Tim A.; North, Laurence J.; Best, Angus I.; Rouméjon, Stéphane; ,
Abstract: Serpentinized peridotites co-exist with mafic rocks in a variety of marine environments including subduction zones, continental rifts and mid-ocean ridges. Remote geophysical methods are crucial to distinguish between them and improve the understanding of the tectonic, magmatic and metamorphic history of the oceanic crust. But, serpentinite peridotites exhibit a wide range of physical properties that complicate such a distinction. We analysed the ultrasonic P - and S -wave velocities ( V p, V s ) and their respective attenuation ( Q p −1, Q s −1 ), electrical resistivity and permeability of four serpentinized peridotite samples from the southern wall of the Atlantis Massif, Mid-Atlantic Ridge, collected during International Ocean Discovery Program Expedition 357. The measurements were taken over a range of loading-unloading stress paths (5–45 MPa), using ∼1.7 cm length, 5 cm diameter samples horizontally extracted from the original cores drilled on the seafloor. The measured parameters showed variable degrees of stress dependence, but followed similar trends. V p, V s, resistivity and permeability show good inter-correlations, while relationships that included Q p −1 and Q s −1 are less clear. Resistivity showed high contrast between highly serpentinized ultramafic matrix (>50 Ω m) and mechanically/geochemically altered (magmatic/hydrothermal-driven alteration) domains (<20 Ω m). This information together with the elastic constants ( V p / V s ratio and bulk moduli) of the samples allowed us to infer useful information about the degree of serpentinization and the alteration state of the rock, contrasted by petrographic analysis. This study shows the potential of combining seismic techniques and controlled source electromagnetic surveys for understanding tectonomagmatic processes and fluid pathways in hydrothermal systems.